До питання про стан наукової сфери та її фінансове забезпечення в Україні - Землянкін, А.І.; Підоричева, І.Ю.; Чекіна, В.Д. (Економіка промисловості, 2013)
Проаналізовано науково-технічний потенціал і стан фінансового забезпечення наукової і науково-технічної діяльності України, подано пропозиції щодо посилення конкурентоспроможності наукової сфери як головного джерела економічного зростання.
Ключові слова: наукова і науково-технічна діяльність, фінансування науки, наукоємність ВВП, інновації. Проанализирован научно-технический потенциал и состояние финансового обеспечения научной и научно-технической деятельности Украины, даны предложения по усилению конку-рентоспособности научной сферы как основного источника экономического роста.
Ключевые слова: научная и научно-техническая деятельность, финансирование науки, наукоемкость ВВП, инновации. In the article the scientific and technical potential of Ukraine and Donetsk region as one of the leading regions is analyzedby the level of development of science, education and production sphere. It is determined that currently Ukraine has a powerful intellectual potential with ability to generate scientific ideas of world level. In spite of this, the extent of influence of scientific and technical potential on economic growth remains insignificant. The problem of manufacturing application of scientific achievements has become one of the burning issues for the Ukrainian science. One of the reasons of such problems is the absence of an appropriate level of financial provisionatthe all stages of innovation process: generation, distribution and consumption of knowledge in the economy. The actual expenditures of the state budget on science are almost six times less than the legally fixed ones. In terms of such a financing the science in Ukrainian society performs primarily cognitive and socio-cultural functions although in the world practice it is well known that the possibility of the science to influence on the level of economic development occurs when its funding is more than 0.9% of GDP. Underfunding of the scientific sphere leads to the outflow of scientific personnel by travelling abroad, precipitous decline in the current logistical and equipment base of research, use of the "catching up"model of economic development, and growing role of foreign investors.
Under the conditions of new world realities the development of the national economy is possible by the restoration of scientific sphere for self-breakthroughs in innovation, firstly in the narrow field of natural or inherited advantages of national industry. At all levels a clear understanding should exist that without a radical increase in government contributions to the education and science nothing really innovative will appear in Ukrainian economy.
Therefore the competitiveness of the scientific sphere and its influence on economic development should be strengthened, including through the implementation of such activities: increase in the share of budget funding for science; improve the legal base in the sphere of scientific and technical activities; use fiscal instruments to attract private sector to the field of science; develop the innovation infrastructure for the system of scientific institutions etc.
Keywords: scientific activities, scientific and technical activities, funding for science, knowledge intensity of GDP, innovations.